Improving future fish consumption: A case study on developing fish products for preschool children - Hui Jia; Zdeněk Fuka; Jan Hora; Magdalena Marešová; Věra Adámková; Koushik Roy; Jan Mraz (Aquaculture Reports)
This study investigates the sensory, nutritional, and microbiological characteristics of various fish products designed for kindergarten consumption. In sensory evaluations, products with 1.6 % salinity were preferred over the adult-oriented 2 %, with sausages, fish kebab, and balls being favored, indicating a predisposition for conventional meat product shapes. Preferred colors were pinkish and yellow, but shape was deemed the most significant factor for appeal. Taste tests showed preferences for standard children snack seasoning, cranberries, and herbs, with scores of 77.5, 72.5, and 60, respectively. Notably, positive motivational strategies by teachers significantly improved children’s acceptance of the fish products. Among the tested items, fish pates, balls, ham, and sausages rated highest, while responses to fish spread were moderate. Microbiological analysis confirmed all products met European (EU) standards with Listeria monocytogenes levels (0 before product left producer, <10 CFU/g during 3-week shelf-life), ensuring safety. Nutritional assessments highlighted balanced protein (14.3–17.2 g/100 g) and varied fat contents (6.6–18.3 g/100 g), with salt levels (1.54–1.7 g/100 g) significantly lower than traditional smoked products, aligning with healthier standards for children. The omega-3 fatty acid content (Eicosapentaenoic Acid (EPA) + Docosahexaenoic Acid (DHA) 265 mg/ 100 g in fish ham to 1067 mg/ 100 g in fish sausages) exceeded recommended daily intake of EPA+DHA (>100 %; average 233 %), underscoring health benefits, especially from other boneless parts of fish beyond just fillets. Economic evaluations indicated that production costs varied (cost: 3.69–7.19 USD/kg, price: 5.51–10.71 USD/kg excluding taxes) inversely with the use of fish fillets versus fish baader. Oxidative stability tests showed malondialdehyde concentrations (<0.8 µg/g) remained within acceptable limits over 20 days chilled-storage, ensuring product integrity. These findings highlight the impact of shape, color, and educator motivation on children's preferences and a strategic approach to developing fish-based preschool meals that could foster healthier eating habits among children.